Carcinogenic Risks in CT Scans: Advancements in Imaging Technology and Radiation Safety - Dave, Vedant; Chandrashekar, Shriya (International Journal of Research in Interdisciplinary Studies, 2025)
This literature review analyzes the past, present, and future of CT (CT) scans with a focus on their carcinogenic qualities. This paper investigates concerns about radiation exposure and its association with cancer risk, supported by mul-tiple studies linking CT scan radiation to increased cancer incidences. Findings have linked CT scans with increased cancer incidence, yet there is limited dis-cussion on how advances in technology mitigate these concerns. This study addresses this gap by analyzing the risks and emerging innovations that reduce radiation exposure. This case study will analyze advances that may be possible and attempt to predict the path of a CT scan. For methodology, we used a systematic review of peer-reviewed articles from databases such as PubMed, DOAJ, and The Mayo Clinic. We combined results from different papers and developed on the topics listed above, providing a sys-tematic review and a probe for discussion. Findings indicate that individuals exposed to CT scans before the age of 22 have a 24-48 percent increased risk of hematological malignancies. However, emerging techniques such as low-dose CT (LDCT) protocols have reduced radiation exposure by up to 32 percent while maintaining diagnostic accuracy. Advances in artificial intelligence (AI) and photon-counting detectors further enhance imaging quality while mitigat-ing risks. This paper highlights CT scans’ dual role as a technological break-through and a potential health risk. Findings indicate that improved technology and patient safety protocols are lowering risk, yet future research should focus on optimizing radiation dose reduction strategies while ensuring early cancer detection remains effective.